2019
DOI: 10.1017/qua.2019.72
|View full text |Cite
|
Sign up to set email alerts
|

Landscape changes in the southern Amazonian foreland basin during the Holocene inferred from Lake Ginebra, Beni, Bolivia

Abstract: Our study is located in northern Beni and aims to improve knowledge on regional landscape changes from the last 8600 years, based on pollen and charcoal analyses from a lacustrine sediment core from Lake Ginebra. Our results showed that gallery forest and lacustrine sediment were observed from 8645 until 3360 cal yr BP. After a change from a lacustrine to a swamp environment at 1700 cal yr BP, the Cerrados and the Mauritia swamp became installed 1000 years ago on our study site. The environmental changes we ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 72 publications
(125 reference statements)
0
4
0
Order By: Relevance
“…This reflects differences in pollen deposition between lakes and swamps. In addition, during wetter intervals both sites showed an increase in the concentration of medium-sized pollen grains, which was more evident in VGE-17 than in LFB1, even if the concentration of small-sized pollen grains appeared to be higher than that of medium-sized pollen grains during the three dry intervals (Escobar-Torrez et al 2023). The fact that LFB1 displayed lower pollen concentrations during wetter intervals was expected, particularly as the influence of the river on the lake is minimal or non-existent (Xu et al 2016).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…This reflects differences in pollen deposition between lakes and swamps. In addition, during wetter intervals both sites showed an increase in the concentration of medium-sized pollen grains, which was more evident in VGE-17 than in LFB1, even if the concentration of small-sized pollen grains appeared to be higher than that of medium-sized pollen grains during the three dry intervals (Escobar-Torrez et al 2023). The fact that LFB1 displayed lower pollen concentrations during wetter intervals was expected, particularly as the influence of the river on the lake is minimal or non-existent (Xu et al 2016).…”
Section: Discussionmentioning
confidence: 96%
“…In both cores, pollen deposition changed depending on water availability, although in different ways. In the case of LFB1, an increase in the accumulation of terrestrial pollen was linked with a reduction in aquatic plant pollen deposition, which was interpreted as a reduction in the lake water level that had allowed terrestrial vegetation to advance toward the coring site, thus increasing terrestrial pollen deposition (Escobar-Torrez et al 2023). In VGE-17, a reduction in terrestrial pollen deposition was observed as water level-related pollen taxa deposition decreased too (indicating the Mauritia palm swamp had dried out) toward the top of the core; conversely, when water availability increased (probably as a result of a wider drainage), the swamp was replaced by arboreal elements (gallery forest), as observed at the bottom of the core.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations